Rancang Bangun Aplikasi Sistem Pendukung Keputusan Kenaikan Jabatan Pegawai Dengan Menggunakan Metode Multi Criteria Decision Making (MCDM) - Riandy Putratama Nasution; Supiyandi; Muhammad Amin (Bulletin of Information Technology (BIT), 2023)
The system for increasing employee positions at the Dinas Perkebunan dan Peternakan of North Sumatra Province has still been carried out using a computer, but the system used is only for inputting data and is not integrated, so it does not rule out the possibility that decision making is carried out subjectively by only looking at it from one side. In certain aspects, of the promotion process, employees who only look at their daily habits at work are not effective. Seeing the existing problems, a decision support system is needed that can help solve problems in decision-making by adjusting the criteria and weights that have been determined by the agency. The method used in decision-making is a multi-criteria decision-making method, with this method we can find out employee data included in the weights and criteria for promotion at the Dinas Perkebunan dan Peternakan of North Sumatra Province. There are problems with the Department of Agriculture and Animal Husbandry of North Sumatra Province requiring a Decision Support System in determining employee promotions. The system development method using the waterfall model is a systematic and sequential software development that will be built using a programming language. The final result of this research is the creation of a Decision Support System for Employee Promotion at Dinas Perkebunan dan Peternakan of North Sumatra Province based on integrated co-opterization can determine promotions for employees who are worth considering and have not been selected to choose the best one in the completeness of the position file. After the decisions obtained in the decision support system application, the system will display the results of the decisions that have been taken.